(untitled) (Международный научный журнал «Инженер», 2026)
The paper details the process of generalizing the classical Viyet formula expressed as infinite products of the number using Rademacher functions. This study presents the mathematical foundations of Rademacher functions and their application to the Viyet formula, which led to various forms of the number expressed as infinite products. These products have not been previously identified or have been insufficiently investigated in previous scientific works. The approaches proposed in the paper open the possibility of identifying new, previously unknown forms of infinite products.